Monoclonal antibodies that define canine homologues of human CD antigens: summary of the First International Canine Leukocyte Antigen Workshop (CLAW). - Cobbold, S; Metcalfe, S (1994)
A panel of 127 monoclonal antibodies against canine leukocyte antigens, including controls, was distributed to 29 laboratories that performed a variety of experiments to identify groups of antibodies against the canine equivalents of some of the human CD antigens. Cluster analysis was performed centrally, using the submitted antibody binding data from immunofluorescence, ELISA and immuno-histology experiments. Immunoprecipitation for molecular weight determination was also performed centrally with T-cell blasts and a B-cell line as the sources of antigen. Clusters of three or more antibodies were found that defined the canine equivalents of the CD5, CD4, CD8 and Thy-1 antigens, and these could be used to label T-cell subsets from the peripheral blood. Other groups of monoclonal antibodies recognized the canine homologues of the CD11/18 group of antigens, CD44 and the CD45/CD45R antigen family: these should be useful in isolating functional subsets of CD4+ helper T cells. There was a cluster of four antibodies that bound strongly to platelets (probably CD41 antigen), three antibodies that were specific to B cells (including CD21) and two antibodies against a granulocyte antigen (possibly CD15). A number of reagents were found against canine MHC-II and immunoglobulin, with some of the latter able to distinguish between Ig subclasses. Properties of each of the canine antigens defined by these monoclonal antibodies are discussed and compared with other species. The availability of such a panel of reagents should allow rapid improvements in the immunological diagnosis of canine disease, and there might now be a potential for testing novel therapeutic strategies in a clinical veterinary setting.